Evolution of the coastal landscape in eastern Veneto: new data from preventive archaeology - Alessandro Pellegrini; Alessandro Asta (Firenze University Press, 2020)
A preventive archeology study was recently conducted in the Caorle area (Province of Venice). Several new datasets have been now managed by computerized analysis with the aim of protect archaeological heritage and, possibly, to realize new predictive models for archaeological research and for landscape management.
Keywords: Coastal Landscape; Underwater archaeology; Remote sensing